The inhabitants of Albacete welcoming the International Brigades. Photo copied from: R 702/104, p. 112. Copied from collection Museum für Deutsche Geschichte (1937)
The inhabitants of Albacete welcoming the International Brigades. Photo copied from: R 702/104, p. 112. Copied from collection Museum für Deutsche Geschichte.